Tailored Systemic Therapy for Colorectal Cancer Liver Metastases - Carolin Czauderna (MDPI AG, 2021)
Liver metastases are the most common site of metastatic spread in colorectal cancer. Current treatment approaches involve effective systemic therapies in combination with surgical and/or interventional strategies. Multimodal strategies greatly improved clinical outcomes of patients with metastatic colorectal cancer over the last decades. Identification of predictive and prognostic biomarkers helped to comprehensively refine individual targeted treatment approaches and resulted in median overall survival rates of 30 months or longer. Current guidelines, thus, recommend treatment selection according to patients’ performance status, tumor localization and stage as well as the tumor’s molecular and genetic status. Here, we outline the latest developments in molecular decision-making for patients with upfront resectable, potentially or initially unresectable and non/never-resectable colorectal cancer liver metastases.